Effects of a cooling channel on the creep damage and failure probability of planar solid oxide fuel cells - Luo, Yun; Chen, Xuqian; Liu, Rongjun; Jiang, Wenchun (Frontiers in Materials, 2023)
Solid oxide fuel cell (SOFC) is an all-solid-state chemical power generation device that converts chemical energy into electrical energy in an efficient and environmentally friendly way in a medium and high temperature environment. However, the thermal stresses and creep damage are inevitably generated at high temperature, which easy to lead to mechanical failure or failure of the whole SOFC stack. Reducing the thermal stress generated by the uneven temperature distribution inside the SOFC stack has become a key problem to be solved urgently. In this paper, the thermal stress, creep damage and failure behavior under their working conditions were analyzed by finite element method. The cooling channel was proposed to reduce the thermal stress and creep damage after. The results show that adding the cooling channel in SOFC stack can reduce the creep damage and the failure probability. The lower the cooling temperature, the better the cooling effect, the lower the creep damage and failure probability.